Design of Non-Haemolytic Nanoemulsions for Intravenous Administration of Hydrophobic APIs - Line Séguy; Anne-Claire Groo; Didier Goux; Didier Hennequin; Aurélie Malzert-Fréon (MDPI AG, 2020)
Among advanced formulation strategies, nanoemulsions are considered useful drug-delivery systems allowing to improve the solubility and the bioavailability of lipophilic drugs. To select safe excipients for nanoemulsion formulation and to discard any haemolytic potential, an in vitro miniaturized test was performed on human whole blood. From haemolysis results obtained on eighteen of the most commonly used excipients, a medium chain triglyceride, a surfactant, and a solubilizer were selected for formulation assays. Based on a design of experiments and a ternary diagram, the feasibility of nanoemulsions was determined. The composition was defined to produce monodisperse nanodroplets with a diameter of either 50 or 120 nm, and their physicochemical properties were optimized to be suitable for intravenous administration. These nanoemulsions, stable over 21 days in storage conditions, were shown to be able to encapsulate with high encapsulation efficiency and high drug loading, up to 16% (w/w), two water practically insoluble drug models: ibuprofen and fenofibrate. Both drugs may be released according to a modulable profile in sink conditions. Such nanoemulsions appear as a very promising and attractive strategy for the efficient early preclinical development of hydrophobic drugs.